Spatial and Temporal Persistence of Fluorescent Lactiplantibacillus plantarum RS-09 in Intestinal Tract - Zhao, Xiaoyu; Zhao, Chenpei; Yang, Leining; Jiang, Linlin; Zhang, Jianlong; Yu, Xin; Chen, Guozhong; Zhu, Hongwei; Tang, Wenli; Li, Youzhi; Wei, Maolian; Zhang, Xingxiao; et al. (Frontiers in Microbiology, 2022)
The beneficial effects of the probiotic strain Lactiplantibacillus plantarum (formerly Lactobacillus plantarum) are based on its adherence and colonization ability in the gut. However, little is known about the migration and long-term gut colonization of the strain. This study evaluated the gut colonization modes of Lactiplantibacillus plantarum RS-09 to identify the strain with long-term gut colonization potential. We established CFDA/SE-labeled RS-09 to study the temporal and spatial distribution of RS-09 in the intestine as well as to analyze its persistence in different parts of the intestine by flow cytometry. This study has shown that the RS-09 strain maintains strong adhesion abilities under acid (pH 2.5) and base (pH 8.5) conditions. In addition, CFDA/SE can be used as an indicator for the labeling of L. plantarum RS-09 in the intestinal tract in vivo. We established a growth kinetics model of RS-09 to elucidate its persistence in the intestine. In vivo persistence experiments showed that the persistence rate of RS-09 was the highest in the cecum (69.5%) and the lowest in the duodenum (12.8%) at 96h. After 20days, RS-09 was predominantly localized in the cecum and colon steadily. These studies provide new insights into the long-term persistence of L. plantarum in the gastrointestinal tract. The CFDA/SE label system may be used to study the in vivo colonization dynamics of other probiotic strains.